The Effect of Training and Work Environment on Employee Performance through Employee Engagement as an Intervening Variable - Kurahman, Muhammad Taufik; Tyas, Ari Anggarani Winadi Prasetyoning (PT Inovasi Pratama Internasional, 2024)
This research aims to examine the influence of Training and Work Environment through Employee Engagement on Employee Performance at PT. Coway International Indonesia. This research was motivated by employee performance which was not mentioned, so research was carried out to find out which training, work environment and Employee Engagement variables would have the most influence on employee performance at PT. Coway International Indonesia. The population in the study were employees of PT. Coway International Indonesia. Meanwhile, the research sample was taken using a purposive sampling technique and then using a saturated sampling technique, namely all members of the population were used as samples with a total of 100 respondents. This research is quantitative research using the Structural Equation Model - Partial Least Square (SEM-PLS) method. The results of the research show that Training and Work Environment have a positive effect on Employee Engagement, Training and Work Environment have a positive effect on Employee Performance, Employee Engagement has a positive effect on Employee Performance, Training has no positive effect on Employee Performance through Employee Engagement, finally the Work Environment has a positive effect on Performance Employees through Employee Engagement. After conducting research, the author suggests expanding the population to other branches, so that it can represent more answers from Coway International Indonesia employees. Coway International Indonesia throughout Indonesia. Apart from that, you can also add other supporting variables, such as Work Motivation, Job Satisfaction, Reward and Punishment and other variables that are relevant to the novelty of the research.